2012
DOI: 10.1007/s10461-012-0381-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information About the Female Condom on Female Condom Use Among Males and Females from a US Urban Community

Abstract: This study investigates the impact of exposure to information about a relatively new prevention method, the female condom (FC), on actual FC use in a community of adults at risk of HIV/STI. A community-wide survey from a mid-size US city is used to estimate unbiased effects of information about the FC on FC use among sexually active men and women. To control for potential confounders we use propensity score matching which matches the group exposed to FC information to participants who were not exposed, achievi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Our own and other studies of FC use and adoption in the U.S. provide strong evidence of the willingness of heterosexual women to initiate it with minimal education and demonstration of proper insertion, use and disposal, and also indicate interest by their male partners to try it [1318]. Further, studies have demonstrated the value of FC promotion to heterosexual couples, whether or not one partner is HIV infected, which suggests that FC has significant potential for uptake in the general population [1921].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our own and other studies of FC use and adoption in the U.S. provide strong evidence of the willingness of heterosexual women to initiate it with minimal education and demonstration of proper insertion, use and disposal, and also indicate interest by their male partners to try it [1318]. Further, studies have demonstrated the value of FC promotion to heterosexual couples, whether or not one partner is HIV infected, which suggests that FC has significant potential for uptake in the general population [1921].…”
Section: Introductionmentioning
confidence: 80%
“…This partially explains men’s lesser FC knowledge, poorer attitudes toward it, less peer influence to use FC or network exposure to it, and ultimately, less use of it [13, 14, 34]. Especially important is shared information about FC within personal networks, which may explain the greater likelihood that women had at least tried FC even if they had heard some negative things about it [18]. If information in the network were increased among men, more of them might make initial efforts to use the device [35].…”
Section: Discussionmentioning
confidence: 99%
“…Future FC programming requires a tailored strategy to address the complex and gendered issues which exist among youth in South Africa [12,36]. Effective FC programs must include accurate and comprehensive education focused on proper use, skill-building on insertion and negotiation, and follow-up strategies to ensure long-term usage [1,5,6,73,74]. Widespread adoption of the FC as a successful prevention method will require 'proactive, well-planned strategies to integrate the FC into a country's contraceptive method mix' [15].…”
Section: Conclusion and Lessons Learnedmentioning
confidence: 99%
“…In its more than 30 years of existence, the female condom (FC) has been recognized as a safe and effective method for preventing human immunodeficiency virus (HIV), other sexually transmitted infection (STIs) and unintended pregnancy among diverse types of women in both high-and low-resource countries [1][2][3][4][5][6][7][8][9][10][11]. Other than the male condom (MC), it is the only female-initiated prevention option that protects against both HIV/STI and pregnancy, as microbicides and other femaleinitiated technologies are still undergoing development and preliminary evaluation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we highlight the importance of considering male preferences in contexts where men typically hold high bargaining power within couples. A number of medical studies have shown that introducing female condoms alongside male condoms improves protection rates (Fontanet et al, 1998;Vijayakumar et al, 2006;Mantell et al, 2015;Coman et al, 2013), but have largely overlooked the role of intra-household bargaining. Meanwhile Ashraf et al (2014a) examine the effect of incentives to sell female condoms on sales by agents, but do not study impacts on end users.…”
mentioning
confidence: 99%